Feeding culture as a component of a man's healthy culture (valeology aspect). - Miheenko О.І (Kharkov National Pedagogical University, 2011)
The essence of feeding culture gives the harmony of correlation environment and identifies the life's quality, functional state of organism and human's health is described. The definitions of healthy culture and nutrition are given. Some modern theories, hypotheses, systems and practical nutrition are analysed. The mechanisms of the health - improving or deleterions influences of nutritional substances as psychophysiologic regulators of vital human's life are denoted. The importance of necessity of using nutrition in the healthy life style is based. The rules of health improving nutrition from the point of view of valeology are offered.